2022
DOI: 10.3389/fnmol.2022.1002139
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase activity in the basolateral amygdala is critical for reconsolidation of a heroin reward memory

Abstract: The persistence of drug memory contributes to relapse to drug seeking. The association between repeated drug exposure and drug-related cues leads to cravings triggered by drug-paired cues. The erasure of drug memories has been considered a promising way to inhibit cravings and prevent relapse. The re-exposure to drug-related cues destabilizes well-consolidated drug memories, during which a de novo protein synthesis-dependent process termed “reconsolidation” occurs to restabilize the reactivated drug memory. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
0
10
1
Order By: Relevance
“…The re‐emergence of drug use following a period of abstinence, referred to as relapse caused by heroin‐associated memory, poses a significant challenge for addiction treatment. Studies in rodents and humans have been aimed at targeting the reconsolidation process and inferring with the heroin‐associated memory to reduce craving and sustain abstinence 30–32 . More and more research demonstrated that manipulating heroin‐associated memory after reactivation significantly prevents relapse and reduces drug‐seeking behaviour 33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The re‐emergence of drug use following a period of abstinence, referred to as relapse caused by heroin‐associated memory, poses a significant challenge for addiction treatment. Studies in rodents and humans have been aimed at targeting the reconsolidation process and inferring with the heroin‐associated memory to reduce craving and sustain abstinence 30–32 . More and more research demonstrated that manipulating heroin‐associated memory after reactivation significantly prevents relapse and reduces drug‐seeking behaviour 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents and humans have been aimed at targeting the reconsolidation process and inferring with the heroin-associated memory to reduce craving and sustain abstinence. [30][31][32] More and more research demonstrated that manipulating heroin-associated memory after reactivation significantly prevents relapse and reduces drug-seeking behaviour. 33,34 These studies indicate that pharmacological approaches combined with reconsolidation may be a promising avenue for identifying potential substances to reduce craving in preclinical rat models.…”
Section: Discussionmentioning
confidence: 99%
“…The Epac‐specific agonist, 8‐(4‐chlorophenylthio)‐2′‐O‐methyladenosine‐3′,5′‐cyclic monophosphate (8‐CPT), was obtained from Sigma‐Aldrich (St. Louis, MO, United States). The infusion volume of 8‐CPT in the BLA (dorsoventral: −8.5 mm, mediolateral: ±5.0 mm and rostrocaudal: −2.8 mm) was 10 nmol per side, following the parameters established in previous studies 21 . Hamilton syringes were connected to 30‐gauge injectors (Plastics One) to facilitate the administration of the drug, which was delivered to a depth of 1 mm below the guide cannula within a duration of 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The infusion volume of 8-CPT in the BLA (dorsoventral: À8.5 mm, mediolateral: ±5.0 mm and rostrocaudal: À2.8 mm) was 10 nmol per side, following the parameters established in previous studies. 21 Hamilton syringes were connected to 30-gauge injectors (Plastics One) to facilitate the administration of the drug, which was delivered to a depth of 1 mm below the guide cannula within a duration of 1 min. The drug was allowed to diffuse for an additional 1 min without removing the injection needles.…”
Section: Drug Infusionsmentioning
confidence: 99%
See 1 more Smart Citation